Physician recruitment and retention in New Brunswick: a medical student perspective - Giberson, Mariah; Murray, Joshua; Percy, Edward (Revue canadienne de l’éducation médicale, 2016)
Background: Physician recruitment and retention is a priority for many Canadian provinces. Each province is unique in terms of recruitment strategies and packages offered; however, little is known about how medical students evaluate these programs. The purpose of the current study was to determine which factors matter most to New Brunswick (NB) medical students when considering their location of future practice. Method: A survey of NB medical students was conducted. Descriptive statistics were produced and a linear regression model was developed to study factors predictive of a student’s expressed willingness to practice in NB. Results: 158 medical students completed the online survey, which is a response rate of 55%. Job availability and spouse’s ability to work in the province were ranked as the top factors in deciding where to practice. In the final regression model, factors predictive of an expressed desire to practice in NB include being female, living in NB prior to medical school, attending medical school at Université de Sherbrooke, participation in the NB Preceptorship program, and a desire to practice family medicine. Conclusions: This study provides insight into what medical students consider when deciding where to practice. This research may be used to inform physician recruitment efforts and guide future research into medical education and policy.